STEPPING STONES TO THE COST OF PRODUCTION REPORT. - Robinson, William G. (The Accounting Review, 1964)
At the very heart of a process cost accounting system lies the cost of production report. The report itself contains the details of departmental total and unit costs and the disposition of these costs by transfer to a subsequent department or finished stock and by accumulation of uncompleted work in process at the end of the period. It becomes the basis for the periodic summary entries which measure the flow of product costs through the plant. While the actual preparation of this report does not appear to pose too many problems, the accumulation of the data necessary for its preparation has been a difficult one for many students. The development of definite steps for this purpose might be of considerable benefit to the student, and it is the purpose of this paper to present and illustrate such a procedure. Seven logical cumulative steps has been prepared for each producing department independently in this article. The author hopes that this will be of great help for students preparing such a report.